Misi Akademik / Mohamad Sufian So'aib - So'aib, Mohamad Sufian (Faculty of Chemical Engineering, 2020)
For 2020 September intake, the Faculty of Chemical Engineering aims to attract around 1 50 new students into its Bachelor degree programme. 'Misi Akademik' of Faculty of Chemical Engineering UiTM Pulau Pinang has participated in several exhibitions showcasing the opportunities for higher degree programmes, especially the Bachelor degree Diploma and STPM (or equivalent) graduates. These exhibitions took place at the matriculation and foundation colleges, as well as roadshow organised by the Ministry of Education Malaysia throughout the final months of 201 9 until the first quarter of 2020. In addition, 'Misi Akademik' also received invitation from Matriculation College and university to deliver talk on the Bachelor degree programme offered by the Faculty, as well as online talk which was conducted during 'Move Control Order'.